Modern psychotherapies : a comprehensive Christian appraisal - Jones, Stanton L; Butman, Richard E., 1951- (Downers Grove, Ill. : InterVarsity Press, 1991)
This book attempts to appraise each of the current major psychotherapy theories in the mental health field from the perspective of evangelical Christianity. It is a "dialog" between the supposedly nonreligious therapeutic psychologies and the religious Christian tradition. But it is a dialog where one side of the conversation, that of the Christian faith, is presumed to have the ultimate standing as truth. - Introduction
The integration of Christianity and psychology -- A Christian view of persons -- The dynamic psychologies -- Classic psychoanalysis -- Contemporary psychodynamic psychotherapies
Includes bibliographical references and index
Keywords: Psychotherapy -- Religious aspects -- Christianity; Christianity -- Psychology; Pastoral psychology; Pastoral care; Psychotherapy; Christianity -- psychology; Pastoral Care; Psychotherapy